Association between dietary selenium and zinc intake and risk of dilated cardiomyopathy in children: a case-control study - Maryam Aryafar; Mohammad Mahdavi; Hossein Shahzadi; Yeganeh Rajabpour Ranjbar; Mohammad Hassan Sohouli; Sina Afzal; Asal Neshatbini Tehrani; Danial Fotros; Ghazal Daftari (BMC, 2024)
Abstract Background Dilated cardiomyopathy (DCMP) is characterized by the enlargement and weakening of the heart and is a major cause of heart failure in children. Infection and nutritional deficiencies are culprits for DCMP. Zinc is an important nutrient for human health due to its anti-oxidant effect that protects cell against oxidative damage. This case-control study aimed to investigate the relationship between dietary intake of zinc and selenium and the risk of DCMP in pediatric patients. Methods A total of 36 DCMP patients and 72 matched controls were recruited, and their dietary intakes were assessed via a validated food frequency questionnaire. We used chi-square and sample T-test for qualitative and quantitative variables, respectively. Logistic regression analysis was applied to assess the relationship between selenium and zinc intake with the risk of DCMP. Results After fully adjusting for confounding factors, analyses showed that selenium (OR = 0.19, CI = 0.057-0.069, P trend < 0.011) and zinc (OR = 0.12, CI = 0.035-0.046, P trend < 0.002) intake were strongly associated with 81% and 88% lower risk of pediatric DCMP, respectively. Conclusions This study highlights the protective role of adequate dietary intake of selenium and zinc in decreasing the risk of DCMP in children. Malnutrition may exacerbate the condition and addressing these micronutrient deficiencies may improve the cardiac function. Further studies are recommended to detect the underlying mechanisms and dietary recommendations for DCMP prevention.